Fast estimation of the difference between two PAM/JTT evolutionary distances in triplets of homologous sequences - Dessimoz, Christophe (BioMed Central, 2006)
BACKGROUND: The estimation of the difference between two evolutionary distances within a triplet of homologs is a common operation that is used for example to determine which of two sequences is closer to a third one. The most accurate method is currently maximum likelihood over the entire triplet. However, this approach is relatively time consuming. RESULTS: We show that an alternative estimator, based on pairwise estimates and therefore much faster to compute, has almost the same statistical power as the maximum likelihood estimator. We also provide a numerical approximation for its variance, which could otherwise only be estimated through an expensive re-sampling approach such as bootstrapping. An extensive simulation demonstrates that the approximation delivers precise confidence intervals. To illustrate the possible applications of these results, we show how they improve the detection of asymmetric evolution, and the identification of the closest relative to a given sequence in a group of homologs. CONCLUSION: The results presented in this paper constitute a basis for large-scale protein cross-comparisons of pairwise evolutionary distances.